Profile of Hearing Loss and Related Risk Factors among Geriatric Patients at RSUD Prof. Dr. H. Aloei Saboe - Najmi Rizqa Damopolii; Helen Marie Yuliana Nazaruddin; Muh Nur Syukriani Yusuf; Dian Pratiwi Iman; Sri Manovita Pateda (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Hearing loss is a common health problem in the geriatric population and significantly affects quality of life and independence. This condition is multifactorial, involving interactions between natural degenerative processes, comorbid conditions, environmental factors, and lifestyle factors. This study aims to describe the factors that influence hearing loss among geriatric patients at RSUD (Regional General Hospital) Prof. Dr. H. Aloei Saboe, Gorontalo City. Methods. This study employed a quantitative descriptive survey method involving 63 geriatric respondents at the Internal Medicine Polyclinic who were selected using purposive sampling. Data were collected through questionnaires and physical examinations (Rinne-Weber test at 512 Hz) and were analyzed using univariate analysis with SPSS to determine the frequency distribution of each variable. Results. The majority of respondents (57.1%) experienced sensorineural hearing loss, were aged 60-69 years (79.4%), and were female (74.6%). The dominant comorbid factors were hypertension (42.9%) and a combination of hypertension and diabetes mellitus (22.2%). Regarding environmental factors, 49.2% of respondents lived near sources of noise, while 11.1% reported occupational noise exposure. In terms of lifestyle factors, obesity was found in 25.4% of respondents, while the prevalence of smoking (27%) and alcohol consumption (9.5%) was relatively low. Conclusion. The study site’s geriatric patients experience predominantly sensorineural hearing loss, with a high proportion of vascular comorbidities among affected patients.